2019
DOI: 10.1097/md.0000000000017387
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bronchial blockers on one-lung ventilation in general anesthesia

Abstract: Background: Double-lumen bronchial tubes (DLBT) and bronchial blockers (BB) are commonly used in the anesthesia for clinical thoracic surgery. But there are few systematic clinical comparisons between them. In this study, the effects of BB and DLBT on one-lung ventilation (OLV) are studied.Methods: The 200 patients with thoracic tuberculosis undergoing thoracic surgery, were randomly assigned to group A (DLBT) and group B (BB). Intubation time, hemodynamic changes (mean arterial pressure [MAP], heart rate [HR]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Correctable causes of arrhythmia, if present, should be identified. The airway must be kept patent ensure proper ventilation (61,62). Intraoperative application of bronchodilators can reduce bronchospasm (63)(64)(65).…”
Section: Anesthesiamentioning
confidence: 99%
“…Correctable causes of arrhythmia, if present, should be identified. The airway must be kept patent ensure proper ventilation (61,62). Intraoperative application of bronchodilators can reduce bronchospasm (63)(64)(65).…”
Section: Anesthesiamentioning
confidence: 99%
“…Zheng et al and Yan et al reported that the use of a bronchial blocker for lung collapse provides an adequate surgical field of vision. 9,16) The MAP of group B was significantly lower than that of group A at T2 and T3. The incidence of intraoperative hypotension in group B was significantly higher than that in group A. Mohtar et al also reported no significant change in blood pressure before, during, or after bronchial blocker use.…”
Section: Discussionmentioning
confidence: 91%
“…Zheng et al and Yan et al reported that the use of a bronchial blocker for lung collapse provides an adequate surgical field of vision. 9 , 16) …”
Section: Discussionmentioning
confidence: 99%
“…Prolonged stimulation of the bronchus by DLT may also contribute to the increasing risk of PPCs. The effects of BB and DLT for lung isolation on PPCs had been evaluated, but with conflicting results (13,14). In the recent randomized controlled trial, authors reported that implementation of BB for patients with thoracic tuberculosis undergoing thoracic-approach debridement had lower incidence of postoperative complications including hoarseness, pharyngalgia and pulmonary infection within 1 week after surgery when compared with DLT (13).…”
Section: Discussionmentioning
confidence: 99%
“…The BB is inserted inside a SLT previously placed into the trachea, while the blood or secretions from the operative lung may expose the contralateral lung to contamination. Several studies of different airway devices (DLT or BB) for lung isolation on PPCs showed different results ( 13 , 14 ). A randomized controlled study showed that implementation of BB has lower incidence of pulmonary infection within 1 week after thoracic surgery than DLT ( 13 ).…”
Section: Introductionmentioning
confidence: 99%